Reflexões preliminares sobre comunidade LGBTQIA+ e Teoria Queer nos estudos informacionais - Mosso, Erick Faria (Universidade Federal de São Carlos, 2022)
The study developed starts from a research problem that is located in the need for investment and deepening in research related to the LGBTQIA+ community, in the scope of Library and Information Science. It starts from the hypothesis that, although increasing, the number of scientific production in the area, on the subject, would still be incipient, given the Brazilian social configuration in relation to the proportionality of this community in the country. More specifically, it considers that Queer Theory, by Judith Butler, could form the basis for the construction of a discussion matrix of informational studies, to foster the area, in the construction of concepts, theories and methodologies of informational studies, consistent with the demands of this community. In order to verify the indicated assumptions, the specific objectives of the research were delimited, to briefly present the context of Queer Theory and to verify how the quantification of scientific production on subjects related to LGBTQIA+ themes is, initially in international databases in Library Science and Science. information, and then in national databases of the area. In the end, the objective was to build a general analysis of how scientific works on the subject are being produced. As a methodological contribution, an exploratory research was developed, based on a bibliographical and documental survey. The international databases listed were: Information Science & Technology Abstracts Library, Information Science & Technology Abstracts with Full Tex; Library and Information Science Abstracts. The national databases listed were BRAPCI, RPPBCI and the FEBAB Repository. The resource used to analyze the bibliographic and documental productions was content analysis, in order to cover some themes about the LGBTQIA+ community that are under discussion in informational studies, a theoretical body was carried out articulating the subjects and later approaching the Queer Theory that was found necessary as a critical proposition for Information Science in its activities. As a result, it was concluded that there is a contribution of Queer Theory to the Organization of Knowledge.
Preliminary reflections on LGBTQIA+ community and Queer Theory in informational studies
Keywords: LGBTQIA+; Teoria Queer; Biblioteconomia e Ciência da Informação; Queer Theory; Librarianship; Information Science; Gênero; Biblioteconomia Social; Social Librarianship; Gener; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA::PROCESSOS DE DISSEMINACAO DA INFORMACAO